(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study examines the synergy between the Merah Putih Cooperative (KMP) and non-bank financial institutions (LKNB) as a strategy for strengthening village economic governance in Indonesia. The research uses a systematic literature review approach with stages of searching, selecting, and analysing sources. Data was collected from scientific journal articles, official government reports, and relevant national institution publications for the period 2021–2025, then analysed thematically to identify patterns of cooperation, benefits, and implementation challenges. The results of the study show that KMP as a community-based economic empowerment instrument has great potential to be strengthened through collaboration with LKNB, such as pawnshops and multifinance companies, especially in the distribution of inclusive microcredit, productive financing, and assistance for village community businesses. This synergy contributes to increased transparency in village fund management, diversification of financing sources, and local economic sustainability, while reducing villages’ dependence on central government subsidies. The findings of this study emphasise the importance of strengthening the capacity of cooperative managers and providing adaptive regulatory support so that the synergy between KMP and LKNB can be effective in promoting village economic independence